Formation of polymer structure by thermally-induced phase separation for a dye-doped liquid crystal light shutter. (April 2019) - Choi, Yeongyu; Oh, Seung-Won; Choi, Tae-Hoon; Yu, Byeong-Hun; Yoon, Tae-Hoon
Abstract: A dye-doped LC/polymer light shutter with a polymer structure that is formed using the thermally-induced phase separation (TIPS) method is demonstrated. The TIPS method does not include any chemical reaction, and thus there is no degradation of the dye during the fabrication process. The light shutter can be fabricated quickly because the optical performance is not affected by the cooling time. The fabricated TIPS cell exhibits excellent optical performance, such as a low haze value of 0.5% in the initial transparent state, and a high haze value of 99.1% in the opaque state with a superior black color. This approach can be used for the high image quality of see-through displays using organic light-emitting diodes. Highlights: We report the fabrication of an initially-transparent dye-doped LC/polymer light shutter. The fabricated cell exhibits very low haze in the initial transparent state, and high haze in the opaque state. Thermally induced phase separation method has easy fabrication process and reduces the fabrication time. Our fabricated cell shows superior black color without dye degradation.